OPTIMALISASI CITRA PRODUK UMKM UNTUK MENINGKATKAN DAYA TARIK KONSUMEN - Ima Fitriani; Al Buchori; Zahra Amelia Putri; Aliffah Putri Maharani; Fotina Waruwu; Deva Nata Nugraha (Adiba Aisha Amira, 2026)
This community service program aims to increase the strong selling power of Micro, Small, and Medium Enterprises (MSMEs) by optimizing product image to enhance consumer attractiveness. The main problem identified is that the product image of MSMEs is still weak, which reduces consumer interest and affects market competitiveness. Many MSME products lack a strong branding identity, resulting in lower purchasing decisions.The method used in this activity is observation. Data were collected through direct observation of MSME product conditions, including branding elements and consumer responses. This method helps identify weaknesses in product presentation and provides a basis for improvement strategies.The results show an increase in sales after the implementation of product image improvement efforts. MSME products become more attractive to consumers, which leads to higher purchasing interest. This indicates that strengthening product image has a positive impact on sales performance. Overall, the program proves that optimizing product image is an effective strategy to increase consumer attractiveness and improve MSME sales.